A result on generalized derivations on right ideals of prime rings - Argaç, N.; Demir, Ç. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Let $R$ be a prime ring of characteristic not 2 and let $I$ be a nonzero right ideal of $R$. Let $U$ be the right Utumi quotient ring of $R$ and let $C$ be the center of $U$. If $G$ is a generalized derivation of $R$ such that $[[G(x), x], G(x)] = 0$ for all $x \in I$, then $R$ is commutative or there exist $a, b \in U$ such that $G(x) = ax + xb$ for all $x \in R$ and one of the following assertions is true:$$(1)\quad (a - λ)I = (0) = (b + λ)I \;\;\text{for some}\; λ \in C,$$$$(2)\quad (a - λ)I = (0) \;\;\text{for some}\; λ \in C \;\;\text{and}\; b \in C.$$